Effect of simultaneous addition of 1D and 3D artificial pinning centers in hybrid YBa2Cu3O7-x multilayers - Mele P.; Adam M.I.; Suzuki T.; Yoshida Y.; Awaji S.; Ichinose A.; Saini S.; Jha A.K.; Matsumoto K. (American Scientific Publishers, 2023)
The nanoengineering approach by PLD method can produce a variety of complex nanocomposite oxide thin films with unique properties for sustainable applications. We report on the epitaxial growth and superconducting properties of YBa2Cu3O7-x (YBCO) multilayers incorporating BaSnO3 (BSO) nanorods and Y2O3 nanoparticles at the same time in order to combine the advantages of both columnar (1D, BSO) and isotropic (3D, Y2O3) pinning with the purpose of enhance the pinning force of the films for a wide range of applications in large external magnetic fields. Multilayered films, alternating YBCO+Y2O3 and YBCO+BSO layers were grown in pulsed laser deposition chamber by switching a surface-modified YBCO+~2A% Y2O3 target and a mixed YBCO+4 wt% BSO target. Different combinations for films' growth have been tried via varying the thickness of the alternating layers. The best result was obtained with the combination [(90 nm YBCO +BSO)/(30 nm YBCO+Y2O3)]3 presenting a maximum global pinning force Fmax p = 17.6 GN/m3 (77 K, 2.2 T, B//c), more than 3 times larger than for typical pure YBCO films. These results demonstrate that the nanoengineering approach is at very advanced level: satisfactory control of nanodefects size and distribution was achieved. At the end, a renewed approach based on the Ginzburg-Landau single vortex theory is used to discuss the contributions of 1D, 3D and 1D+3D APCs to the global pinning force of the hybrid multilayers. 2017 by American Scientific Publishers.